A case study of maximum velocity sprint running performance and technique changes within an elite training group - Bezodis, I.; von Lieres und Wilkau, H.; Simpson, S.; Irwin, G. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to identify the effect of a structured training programme on sprint performance and technique in three individual experienced sprinters. Velocity, step length, step frequency, temporal variables and segment angles were gathered from 50 m maximal sprints before and after two high volume four-week training blocks. Participantspecific analyses revealed that athletes` performance responded differently to training. Changes in velocity between sessions were attributable to different underlying variables across athletes, which matched with expectations based upon coaching observations. These findings have important implications for the design of sprint training programmes and for the timing of applied biomechanical data collection sessions for the purpose of analysis and feedback to coaches and athletes.